Effect of Informal Employment on Overeducation in Developing Countries with a focus on the Democratic Republic of Congo (DRC) - Cédrick Kalemasi Mosengo; Christian Marie Zamo Akono (African Governance and Development Institute (AGDI), 2024)
The aim of this study is to assess the effect of informal employment on the occurrence of overeducation in developing countries, focusing on the specific case of the DRC. Using employment data, we determine the incidence of overeducation and we isolate the role of informal employment as a determinant of overeducation. To measure overeducation, we mainly use the normative (adequationist) approach. We find an incidence of overeducation in the order of 33.3% in the DRC labor market. The econometric results based on recursive bivariate Probit suggest a positive and significant effect of informal employment. The results found are robust even when using the statistical approach as an alternative measure of overeducation. These findings suggest a set of measures likely to reduce the incidence of overeducation on the labor market. These should focus on the formalization of informal sector employment and policies to improve labor market matches.
Keywords: E26; E24; I21; J24; 330; Skills mismatch; Overeducation; Undereducation; Informal employment